2016
DOI: 10.1002/chem.201603398
|View full text |Cite
|
Sign up to set email alerts
|

“Shine & Click” Photo‐Induced Interfacial Unmasking of Strained Alkynes on Small Water‐Soluble Gold Nanoparticles

Abstract: In this study, we report the design, synthesis, and characterization of small 3 nm water soluble gold nanoparticles (AuNPs) that feature cyclopropenone-masked strained alkyne moieties capable of undergoing interfacial strain-promoted cycloaddition (i-SPAAC) with azides after exposure to UV-A light. A strained alkyne precursor was incorporated onto AuNPs by direct ligand exchange of a thiol-modified cyclopropenone-masked dibenzocyclooctyne (photoDIBO) ligand. These photoDIBO-AuNPs were characterized by H NMR, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…Luo et al. also developed a “Shine and Click” approach for functionalising the surface of bioactive nanoparticles …”
Section: Photoactive Reagents That Induce Cycloadditionsmentioning
confidence: 99%
“…Luo et al. also developed a “Shine and Click” approach for functionalising the surface of bioactive nanoparticles …”
Section: Photoactive Reagents That Induce Cycloadditionsmentioning
confidence: 99%
“…A subsequent study showed that Caenorhabditis elegans and zebrafish embryos could also undergo in vivo labeling with cyclooctyne‐functionalized fluorophores, allowing for spatiotemporal imaging of cell surface glycosylation [33–37] . Since then, this reaction has been used for tissue engineering, [5] radiolabeling, [19] antibody–drug conjugates, [38] cell encapsulation, [39] the preparation of polymeric gels, [40, 41] and the development of nanomaterials [42, 43] …”
Section: Introductionmentioning
confidence: 99%
“…In particular, a thiolated strained cyclooctyne molecule, which represents the most obvious route towards functionalizing gold, cannot be stably obtained due to self-reactivity via thiol-yne addition. [20][21][22] To overcome this synthetic challenge, our group previously developed the use of cyclopropenones as photochemical alkyne precursors on gold nanoparticles (AuNPs) [23][24] , a chemical system adapted from Popik et al who first utilized cyclopropenone-masked dibenzocyclooctynes to label living cells, 25 and then to functionalize polymer brushes and immobilize azido molecules via SPAAC. 26 This method allowed us to synthesize a thiol precursor and assemble it onto AuNPs directly.…”
Section: Introductionmentioning
confidence: 99%